Pengaruh Pelatihan Kerja, K3, dan Lingkungan Kerja terhadap Kinerja Pegawai pada Dinas Lingkungan Hidup Kabupaten Boyolali - Anisa Putri Anggraini; Hari Purwanto; Unna Ria Safitri (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to determine the effect of job training, occupational safety and health (OSH), and work environment on employee performance at the Environmental Agency of Boyolali Regency. The research method used was a quantitative approach, with data collected through questionnaires distributed to 54 respondents. Data were analyzed using SPSS version 26. The results of the hypothesis testing (t-test) indicate that job training does not have a significant effect on employee performance, with a significance value of 0.808 > 0.05. Occupational safety and health (OSH) also do not have a significant effect on employee performance, with a significance value of 0.612 > 0.05. Meanwhile, the work environment has a positive and significant effect on employee performance, with a significance value of 0.000 < 0.05. The simultaneous test (F-test) shows that the three independent variables jointly have a significant effect on employee performance. The coefficient of determination is 0.552, indicating that the independent variables explain 55.2% of the variation in the dependent variable, while the remaining 44.8% is influenced by other variables not examined in this study.